Complexity of Illness and Adjunctive Benzodiazepine Use in Outpatients With Bipolar I or II Disorder. Issue 1 (February 2015) - Bobo, William V.; Reilly-Harrington, Noreen A.; Ketter, Terence A.; Brody, Benjamin D.; Kinrys, Gustavo; Kemp, David E.; Shelton, Richard C.; McElroy, Susan L.; Sylvia, Louisa G.; Kocsis, James H.; McInnis, Melvin G.; Friedman, Edward S.; et al.
<x xml:space="preserve">Abstract</x> Abstract Benzodiazepines are widely prescribed for patients with bipolar disorders in clinical practice, but very little is known about the subtypes of patients with bipolar disorder or aspects of bipolar illness that contribute most to benzodiazepine use. We examined the prevalence of and factors associated with benzodiazepine use among 482 patients with bipolar I or II disorder enrolled in the Bipolar CHOICE study. Eighty-one subjects were prescribed benzodiazepines at study entry and were considered benzodiazepine users. Stepwise logistic regression was used to model baseline benzodiazepine use versus nonuse, using entry and exit criteria of P < 0.1. In bivariate analyses, benzodiazepine users were prescribed a significantly higher number of other psychotropic medications and were more likely to be prescribed lamotrigine or antidepressants as compared with benzodiazepine nonusers. Benzodiazepine users were more likely to have a diagnosis of bipolar I disorder and comorbid anxiety disorder, but not comorbid alcohol or substance use disorders. Benzodiazepine users also had experienced more anxiety and depressive symptoms and suicidality, but not irritability or manic symptoms, than did benzodiazepine nonusers. In the multivariate model, anxiety symptom level (regardless of diagnosis), lamotrigine use, number of concomitant psychotropic medications, college education, and high household income predicted benzodiazepine use. Benzodiazepine use in patients with bipolar disorders is associated with greater illness complexity as indicated by a higher number of concomitant psychotropic medications and higher anxiety symptom burden, regardless of a comorbid anxiety disorder diagnosis. Demographic factors were also important determinants of benzodiazepine use, which may be related to access to care and insurance coverage for benzodiazepines.